2023
DOI: 10.3390/agronomy13041085
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress and Development Trends of Greenhouse Gas Emissions from Cereal–Legume Intercropping Systems

Abstract: High yields and low carbon emissions are new challenges for modern crop production. Balancing the crop yield and reducing greenhouse gas (GHG) emissions has become a new field of agronomic technology innovation. Cereal–legume intercropping is a typical diversification planting system, which has been expected to achieve the dual goals of high production and low GHG emissions. However, the synergistic effect of integrating various technologies in an intercropping system on GHG emissions and whether it will achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…However, the current study reveals that about 38% of organic elds in the region have N content above 190 kg ha − 1, whereas 56.25% of chemicalized elds show N content above that critical level. However, the chemicalized elds show a signi cantly high percentage of global warming potential; the data indicate that some of the organic elds are similar to the chemicalized elds in N content, especially the 3.52% elds showing N > 560 kg ha − 1 because the natural means to control freely available N in the eld soil (Yao et al, 2023) per organic agricultural norms are not found in such elds. Another reason for an excessive N in organic elds is the application of poultry manure rich in N content by farmers in organic areas without a limit.…”
Section: San Over Organic and Chemicalized Eldsmentioning
confidence: 93%
“…However, the current study reveals that about 38% of organic elds in the region have N content above 190 kg ha − 1, whereas 56.25% of chemicalized elds show N content above that critical level. However, the chemicalized elds show a signi cantly high percentage of global warming potential; the data indicate that some of the organic elds are similar to the chemicalized elds in N content, especially the 3.52% elds showing N > 560 kg ha − 1 because the natural means to control freely available N in the eld soil (Yao et al, 2023) per organic agricultural norms are not found in such elds. Another reason for an excessive N in organic elds is the application of poultry manure rich in N content by farmers in organic areas without a limit.…”
Section: San Over Organic and Chemicalized Eldsmentioning
confidence: 93%
“…The use of legume species in crop rotation of organic sweet corn production systems is inevitably practiced to maintain the quality of land resources and sweet corn productivity. Although cereallegume intercropping is a typical planting strategy for diversification that has been developed to accomplish the double objectives of high output and low greenhouse gas emissions (Yao et al, 2023), more cereal-legume intercropping research needs to be conducted, especially in organic vegetables production system. A challenge specific to sweet corn-peanut intercropping under organic production systems is ensuring both sweet corn and peanut benefit from this cropping system.…”
Section: Peanut Responsesmentioning
confidence: 99%